1991
DOI: 10.1302/0301-620x.73b1.1670499
|View full text |Cite
|
Sign up to set email alerts
|

Percutaneous screw fixation for fractures of the scaphoid

Abstract: We describe a percutaneous technique for screw fixation of all types of fractures of the scaphoid. During a 15-year period ending in 1984, 280 cases were treated by this method; 198 of them returned for evaluation in 1986 and comprise the material for this report. After a mean postoperative time of 82 months, 89% of the recent fractures had united as well as 81.8% of those with delayed or nonunion and 42.8% of those with sclerotic nonunion.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

2
61
1
11

Year Published

1998
1998
2021
2021

Publication Types

Select...
5
4
1

Relationship

0
10

Authors

Journals

citations
Cited by 132 publications
(75 citation statements)
references
References 13 publications
2
61
1
11
Order By: Relevance
“…The palmar approach has achieved much popularity since its evolution because of the excellent clinical outcome documented by various authors [18,19]. However, recent work by some authors [10,17] has shown that the dorsal approach provides better targeting and more precise placement of the screw.…”
Section: Discussionmentioning
confidence: 99%
“…The palmar approach has achieved much popularity since its evolution because of the excellent clinical outcome documented by various authors [18,19]. However, recent work by some authors [10,17] has shown that the dorsal approach provides better targeting and more precise placement of the screw.…”
Section: Discussionmentioning
confidence: 99%
“…There are several minimally invasive internal fixation techniques for scaphoid fractures (Brauer et al, 1997;Haddad and Goddard, 1998;Inoue and Shionoya, 1997;Ledoux et al, 1995;Wozasek and Moser, 1991). Minimally invasive screw fixation in athletes has been reported to reduce the time to union and to allow a rapid return to sports activities (Rettig and Kolias, 1996;Taras et al, 1999).…”
Section: Introductionmentioning
confidence: 99%
“…9 Inoue and Shionoya 12 have shown a shorter time to union and an earlier return to manual labour when acute fixation is compared with conservative treatment. Early intervention is also supported by Filan and Herbert's operative findings; 2 in 82 acute fractures they noted that they were often in a worse position than suggested by radiographs and that there was soft-tissue interposition in 28.…”
Section: Discussionmentioning
confidence: 97%